The Effects Of Pioglitazone And MK886 ON THE Mrna EXPRESSION OF PPAR-alpha, PPAR-gamma And Its Associated GENES, Cell Death And Migration In MDA-MB- 231 Cancer Cells - Nadarajan, Kalpanah (2015)
Pioglitazone (PGZ) is a prescription drug used in the treatment of diabetes mellitus type II. It is a well-known synthetic agonist for PP AR, and being studied extensively by our research group as a target drug for the treatment of ER-negative breast cancer. The ER-negative breast cancer is more aggressive and fast growing than the ERpositive breast cancer. Moreover, this type of cancer has a poor prognosis generally and is often unresponsive to anti-estrogen therapy. A preliminary research showed that treatment of MDA-MB-231 with PGZ produced little effect on cell growth and did not induce apoptosis in the cancer cells despite increasing the levels of PPARa mRNA expression in the cells. As such, to further evaluate the role of the PPARa mRNA expression in MDA-MB-231, the effects of paz and MK886 on the induction and inhibition of inRNA expression of PPARa, respectively, and other associated genes in MDA:.MB-231 were determined in this study. The biological mechanisms induced by both drugs were also assessed in this study. To achieve all objectives of the study, the mRNA expression levels of PPARa in PGZ-treated and MK886-treated MDA-MB-231 were determined using Real-Time PCR; the growth inhibitory effects of PGZ and MK886 in MDA-MB-231 were determined using the Trypan Blue Exclusion Assay and Real-time PCR; the apoptosis induction by PGZ and MK886 in MDA-MB-231 was determined using the DNA Fragmentation Assay, Real-Time PCR, cell staining and Flow Cytometry, and the migration of PGZ-treated and MK886-treated MDA-MB-231 was determined using the Wound Healing Assay.